Analysis and Motion Modeling of Bionic Auxiliary Device for Ankle Rehabilitation - Wang Liangwen; Li Quntao; Wang Xinjie; Mu Xiaoqi; Xie Guizhong; Du Wenliao (Jixie chuandong)
In order to realize the ankle recovery,a kind of auxiliary device for ankle rehabilitation based on a ball pin vice is developed. The device has two degrees of freedom,while three- dimensional movement of the ankle can be achieved approximately. Based on introducing the structure of the auxiliary device for ankle rehabilitation,the motion modeling and analysis of the device are performed. Aiming at multiple kind of drive patterns of the structure,the modeling analysis of rigid- soft combination drive and rigid drive pattern are conducted respectively. The related calculation formulas are deduced and calculated by Matlab. A process of this research can be as a reference for mechanism analysis of more motion models.